2015
DOI: 10.1063/1.4914469
|View full text |Cite
|
Sign up to set email alerts
|

Streamline based design guideline for deterministic microfluidic hydrodynamic single cell traps

Abstract: A prerequisite for single cell study is the capture and isolation of individual cells. In microfluidic devices, cell capture is often achieved by means of trapping. While many microfluidic trapping techniques exist, hydrodynamic methods are particularly attractive due to their simplicity and scalability. However, current design guidelines for single cell hydrodynamic traps predominantly rely on flow resistance manipulation or qualitative streamline analysis without considering the target particle size. This la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…20,23 Thus, researchers have used computational fluid dynamics analysis in microstructure design more frequently to obtain a more accurate and rapid solution. 24,25 In this work, Comsol was used to obtain the optimal hydraulic resistance distribution in the microchannel. We iteratively optimized the channel design by altering variable parameters of the geometry.…”
Section: B Optimization Of Microchannels and Finite Element Analysismentioning
confidence: 99%
“…20,23 Thus, researchers have used computational fluid dynamics analysis in microstructure design more frequently to obtain a more accurate and rapid solution. 24,25 In this work, Comsol was used to obtain the optimal hydraulic resistance distribution in the microchannel. We iteratively optimized the channel design by altering variable parameters of the geometry.…”
Section: B Optimization Of Microchannels and Finite Element Analysismentioning
confidence: 99%
“…42 As the incoming cells are distributed randomly across the cross-section of the channel, one can increase the probability of cell capture by increasing the ratio of the flow through the trapping pathway over the flow through the bypassing channel (Q trap /Q bypass ). 42, 43 It has been shown that a particle is preferentially directed towards a vacant trapping pathway if and only if Q trap >Q bypass .…”
Section: Trapping Single Cells With Very High Efficiencymentioning
confidence: 99%
“…42 As the incoming cells are distributed randomly across the cross-section of the channel, one can increase the probability of cell capture by increasing the ratio of the flow through the trapping pathway over the flow through the bypassing channel (Q trap /Q bypass ). 42, 43 It has been shown that a particle is preferentially directed towards a vacant trapping pathway if and only if Q trap >Q bypass . 39, 4345 However, increasing the hydrodynamic resistance of the bypass channel by using a lengthy channel causes multiple problems: (1) cell clogging due to a limited shear rate through the bypassing pathway 46 ; (2) high pressure differential exerted on the captured cells 47 ; and (3) multiple particles per trap.…”
Section: Trapping Single Cells With Very High Efficiencymentioning
confidence: 99%
“…166 The authors demonstrated 100% cell trapping with HeLa cells. The device design provides deterministic single cell trapping akin to that demonstrated by Guan et al 162 However, this format does not require long bypass channels to achieve optimum flow resistances. The isolation methods utilizing hydrodynamics and physical obstructions as discussed above are beneficial because they are passive and can be adopted for various cell sizes and shapes.…”
Section: Sample Preparationmentioning
confidence: 99%